Efektivitas Modul Hybrid Project Based Learning (H-Pjbl) Berbasis Laboratorium Untuk Meningkatkan Keterampilan Proses Sains Siswa - Ihsan Nurdiansah; Yanti Sofi Makiyah (Department of Physics Education, Universitas Mataram, 2021)
This study aimed to described the effectiveness of the Laboratory-Based Hybrid Project Based Learning Module to improve students' science process skills. This study uses a quasi-experimental method with a one-group pre-test pre-test design. The research sample was selected randomly from the population of class X TKRO SMKN 1 Manonjaya students. Data analysis was seen from the results of the pre-test pre-test obtained by students, t-test and N-gain to determine the improvement of students' scientific process skills descriptively. The results of the study obtained that the results of the pre-test and post-test of students increased by 37.26%, then the t-test analysis where t_count > t_table obtained a value of 3.54> 1.76 then Ho was rejected so that there was a significant difference between the pretest and posttest scores. after using the laboratory-based Hybrid Project Based Learning module, it can improve students' science process skills (KPS). However, based on the gain value obtained, 0.3 is still categorized as